Hepatitis B virus (HBV) - Olivera-Martinez, Marco (Henry Stewart Talks, 2017)
Virus structure and its genome, Prevention: universal vaccination, Geographic distribution, HBV transmission, Special HBV mechanisms, The immune reaction and different phases, Chronic hepatitis B serology, Viral markers, Risk of becoming a carrier, Available treatments and their goals, Medications, Reistance to antiviral treatment, Mutants, HCC screening, Survival